IMPLEMENTASI PARADIGMA FUNGSIONALISME DURKHEIM DALAM MATA PELAJARAN PPKN KURIKULUM MERDEKA BERBASIS PEMBELAJARAN MENDALAM (DEEP LEARNING) - Esti Perwitasari; Sarmini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of Émile Durkheim’s functionalist paradigm in Pancasila and Civic Education (PPKn) within the Merdeka Curriculum through a deep learning-based approach. The functionalist paradigm views education as a social institution that plays a vital role in maintaining social order, fostering social integration, and preparing students to carry out their social responsibilities effectively in society, the nation, and the state. This study employs a qualitative approach through a literature review by examining various scholarly sources, educational policies, and relevant concepts related to PPKn, the Merdeka Curriculum, deep learning, and Durkheim’s functionalist theory. The findings indicate that the implementation of the functionalist paradigm in deep learning-based PPKn is reflected in learning processes that emphasize meaningful understanding, critical reflection, collaboration, and active student engagement in addressing real-life social issues. Learning activities are not merely oriented toward the acquisition of civic knowledge but also toward the internalization of Pancasila values, character development, social responsibility, and the formation of collective consciousness as citizens. Through the deep learning approach, students are encouraged to connect civic concepts with their everyday experiences, creating a learning process that is more relevant, contextual, and sustainable. This implementation is aligned with the objectives of the Merdeka Curriculum in developing the Pancasila Student Profile, characterized by faith and piety, critical reasoning, independence, creativity, mutual cooperation, and global diversity awareness. Therefore, Durkheim’s functionalist paradigm provides a strong theoretical foundation for the development of PPKn learning that strengthens social integration, fosters national character, and prepares young generations to become democratic, responsible, and adaptive citizens in responding to social change.